The flexibility trainer: Feasibility analysis, prototype- and test station development for a sports device for hip-joint flexibility and strength enhancement - Hölbling, D.; Grafinger, M.; Baca, A.; Dabnichki, P. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
Martial Arts, dancing, and gymnastics are among the sports that depend on outstanding hip-joint flexibility and strength to successfully perform high level techniques. Latest research suggests that flexibility and antagonistic strength are strongly related and require agonistic strength training. Therefore, the aim of the study was to develop a model prototype of a device that utilises flexibility-enhancement reflexes and provides appropriate means for strength training and delivers hip joint range-of-motion (ROM) increase. The device provisionally called Flexibility Trainer (FT) is equipped with sensors that measures and estimate the athletes` hip joint moments during training. The FT aims to utilise the athletes body weight while performing controlled leg spreads. Its main components are a rail system with 2 slides and foot mounts (tiltable and turnable), a hydraulic braking system for force independent constant velocity slide (nearly isokinetic), a force sensor and a holding device . It is hypothesised that the leg-spread movement activates the reciprocal-inhibition reflex and increases antagonistic strength, whereas the leg-closing movement activates the autogenic-inhibition reflex and leads to serial hypertrophy. A model for hip-joint moment calculation based on force sensor and motion capturing data is proposed.